2017
DOI: 10.18632/oncotarget.23202
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IAP’s and activation of p53 leads to caspase-dependent apoptosis in gastric cancer cells treated with Scutellarein

Abstract: Gastric cancer is the fifth most common cancer and the third leading cause of cancer deaths worldwide. South Korea is in first place with 9,180 death alone attributed to gastric cancer in 2013. Plenty of literature suggests the evasion of apoptosis is implicated in neurodegeneration, autoimmune diseases, and tumors development due to dysregulation in the apoptotic mechanism. Reduced apoptosis or its resistance in cancer cells plays a significant role in carcinogenesis. It’s imperative to understand apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
5
15
0
Order By: Relevance
“…Apoptosis is accompanied with a reduction of the G1 phase cells and an increase in the G2/M phase cells, signifying a cell cycle arrest in G2/M phase. Moreover, similar results were observed with previous studies showing that an increase in the number of G2/M phase cells is clearly related to apoptosis [ 31 , 32 ]. In the current study, we found that PEC treatment decreased the percentage of G1 phase and increased sub-G1 and G2/M phase cells.…”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis is accompanied with a reduction of the G1 phase cells and an increase in the G2/M phase cells, signifying a cell cycle arrest in G2/M phase. Moreover, similar results were observed with previous studies showing that an increase in the number of G2/M phase cells is clearly related to apoptosis [ 31 , 32 ]. In the current study, we found that PEC treatment decreased the percentage of G1 phase and increased sub-G1 and G2/M phase cells.…”
Section: Discussionsupporting
confidence: 92%
“…The Bcl/Bax ratio is considered an important determinant of the apoptosis induction [14] and in this study, we found that chrysophanol increased Bax expression and decreased the Bcl-2 expression, thereby causing a remarkable decrease in the Bcl-2/Bax ratio. Apoptosis is also accompanied by the activation of the caspases [15] and in this study, we found that chrysophanol induced the activation of caspase-3 and 9 in a dose-dependent pattern. These observations are also supported by previous studies where chrysophanol has been shown to trigger apoptosis of the breast cancer cells [16].…”
Section: Discussionsupporting
confidence: 68%
“…These findings support the hypothesis that different mechanisms may be responsible for the efficacy of JQ1 in NETs, and these may involve the apoptotic pathway, as indicated by our RNA-Seq analysis that revealed four apoptosis-associated genes (Capn9, Dffb, Birc3 and Nfkb1) to be downregulated by JQ1 treatment. Birc3 encodes cIAP2, which is an E3 ubiquitin protein ligase that is a member of the inhibitors of apoptosis proteins (IAP) family, and increases cIAP2 expression that can lead to evasion of caspase-mediated apoptosis in different cancers including gastric and gallbladder cancers and glioblastoma (Wang et al 2016, Jiang et al 2017, Gowda Saralamma et al 2018. In addition, cIAP2 has been reported to activate NFκB (encoded by Nfkb1) signalling, which also has roles in apoptosis regulation (Tchoghandjian et al 2013, Jiang et al 2017.…”
Section: Discussionmentioning
confidence: 99%